Low cost multi-touch system for face-to-face interaction - Ong, Kian Leong. (2013)
Face-to-face interaction is a form of interaction which involves people doing things while facing each other. Activities such as card games and chatting are examples of activities that are considered face-to-face interactions. However, with the rise of technology such as telephone, Internet, electronic mail, instant message, the amount time spent on face-to-face interactions between people are steadily getting less. Technology-supported group activity created during the past few decades such as console games, television, online games, often direct the user’s attention towards a screen and have been neglecting the face-to-face aspect of communication.